2015
DOI: 10.1093/nar/gkv140
|View full text |Cite
|
Sign up to set email alerts
|

A method for mutagenesis of mouse mtDNA and a resource of mouse mtDNA mutations for modeling human pathological conditions

Abstract: Mutations in human mitochondrial DNA (mtDNA) can cause mitochondrial disease and have been associated with neurodegenerative disorders, cancer, diabetes and aging. Yet our progress toward delineating the precise contributions of mtDNA mutations to these conditions is impeded by the limited availability of faithful transmitochondrial animal models. Here, we report a method for the isolation of mutations in mouse mtDNA and its implementation for the generation of a collection of over 150 cell lines suitable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…We [ 18 ] and others [ 36 ] have shown that intracellular mtDNA cloning using partial depletion with EtBr is an effective means of inducing shifts in heteroplasmy (relative abundance of mtDNA haplotypes). However, prolonged treatment with EtBr represents a rate-limiting step of this procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We [ 18 ] and others [ 36 ] have shown that intracellular mtDNA cloning using partial depletion with EtBr is an effective means of inducing shifts in heteroplasmy (relative abundance of mtDNA haplotypes). However, prolonged treatment with EtBr represents a rate-limiting step of this procedure.…”
Section: Resultsmentioning
confidence: 99%
“…When indicated, uridine and pyruvate were omitted from this medium for selection of cells containing mtDNA (-UP medium). 3T3#52 is a Tet-On derivative of the NIH 3T3 cell line [ 18 ]. 4B6 mouse embryonic fibroblasts were derived from Lig3 flox/flox embryos [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…A lentivirus encoding inducible secreted Gaussia luciferase was also described previously [ 24 ]. 3T3#52 is a Tet-On derivative of the NIH 3T3 cell line [ 25 ]. Plasmids and viral constructs were generated by standard techniques [ 26 ] and their diagrams are presented in the S1 Fig .…”
Section: Methodsmentioning
confidence: 99%
“…Characterization of mutations in mitochondrially encoded OXPHOS complex genes provided evidence for their role in tumor development and progression. Previous studies have demonstrated that mitochondrial mutations are associated with elevated ROS production [27,39], increased invasion ability [40,41], decimated mitochondria copy number [39,42], and higher risk of breast cancer [21], oral squamous cell carcinoma [39,43], colorectal cancer [12,44], and thyroid oncocytoma [39,45]. The existence of empirical evidence for mitochondrial genomic mutations and subsequent mitochondrial dysfunction in several cancers suggests that mitochondrial mutations may have potential in evaluating the risk of cancer progression [19,20,28,39,41,43].…”
Section: Discussionmentioning
confidence: 99%